A need for violence [large type] - Richards, Dusty; Mayo, Matthew P. (Richards, Dusty. Battling Harrigans of the frontier, 2024)
"Spring, 1850. After a brutally long winter in the Rockies, Mack Harrigan and his growing family have learned to manage the harsh realities of frontier life. Their new friends, the Shoshone, have taught them the skills they need to survive in this rugged land, from tracking and hunting to fishing and foraging. But when their camp is attacked by an enemy tribe, the skills the Harrigans need most are those of a Shoshone warrior. Sometimes there is a need for violence. This is one of those times. The attackers are merciless. They crush the skulls of their victims. Slice off their scalps. And kidnap children as prisoners of war. The Harrigans are horrified by the bloodshed and brutality of the attack -- and are determined to fight back alongside the Shoshone. But their mission to save the children will ultimately send the battling Harrigans even deeper into the wild frontier. Farther west than most dare to travel. And closer to finding the American dream -- if they survive . . ."--